Spectrophotometric Determination of Micro Germanium(IV) with 5-(4-Carboxylphenylazo)-8-hydroxylquinoline as Colour Reagent - Du1, Qiu-Jiang; Chen2, Wen-Bin (Asian Journal of Chemistry, 2013)
The colour reaction of chromogenic agent 5-(4-carboxylphenylazo)-8-hydroxylquinoline with Ge(IV) was studied in the presence of micromulsion CTMAB-OP. A novel spectrophotometric determination of trace Ge(IV) with high sensitivity was established. The results showed that in the Na2B4O7-NaOH medium of pH 9.8, 5-(4-carboxylphenylazo)-8-hydroxylquinoline reacted with Ge(IV) could form a red stable complex and the molar ratio of reagent:metal was 3:1. The maximum absorption peak of the complex was located at 558 nm with the apparent molar absorptivity of 2.5 × 105 L mol-1 cm-1. In 10 mL of solution, 0.03-2.8 μg of Ge(IV) obeyed Beer’s law and the detection limit was 0.1 mg/L. The colour reaction system could tolerate many interfering ions due to the existence of ammonia. This method was applied to determination of trace Ge(IV) in tea. The results are in consistency with the results obtained by atomic absorption spectrometric method. Recovery was also tested and values obtained were in the range of 102.5-103.6 % and the RSD (n = 6) of lower than 3.6 %.